Gold nanoholes fabricated by colloidal lithography: novel insights into nanofabrication, short-range correlation and optical properties. Issue 17 (15th April 2019) - Cesaria, Maura; Taurino, Antonietta; Manera, Maria Grazia; Minunni, Maria; Scarano, Simona; Rella, Roberto
Abstract : A simplified colloidal lithography protocol (polyelectrolyte monolayer) for Au nanohole fabrication and autocorrelation/FFT analysis of SEM images to disclose hidden short-range periodicities. Abstract : Colloidal lithography is widely used as a low cost and large-area deposition approach, alternative to the conventional small-area expensive lithographic techniques, for the fabrication of short-range ordered sub-wavelength metallic nanostructures. This paper contributes to the understanding of the impact of the fabrication protocol of a colloidal mask on the optical and sensing properties of short range-ordered nanohole (NH) distributions fabricated by colloidal lithography in optically thin (20 nm thick) gold films. We consider polystyrene nanospheres (PS-NSPs) with a nominal diameter of 80 nm, electrostatically adsorbed from a salt-free colloidal solution onto a polydiallyldimethylammonium (PDDA) countercharged monolayer. By avoiding the conventional polyelectrolyte multilayer and based on the interplay between the deposition times of both PDDA and PS-NSPs, we demonstrate effective simplification of the commonly applied deposition protocol and effective tuning of the NH-to-NH spacing ( d NN ) with negligible agglomeration. Comparison with NH samples prepared by salt-containing colloidal solutions points out the negative impact of salt addition on the optical properties. The effective tuning of d NN obtained by our protocol demonstrates highly correlated disorder under unsaturated adsorption and allows a discussion on the analogies of the optical response between long- and short- range ordered NH systems, which is a still debated topic. By Fast Fourier Transform of autocorrelation images of scanning electron microscopy micrographs we demonstrate quantitatively, rather than in principle, the correspondence between an inherent ordering length-scale and d NN . As optical transducers for detecting refractive index changes, our samples exhibit significant bulk sensitivity (∼309 nm RIU −1 ) in the framework of short range ordered NH systems.